Long‐term outcomes of patients with chronic inflammatory diseases after percutaneous coronary intervention. Issue 5 (14th July 2021) - Marcusohn, Erez; Zukermann, Robert; Kerner, Arthur; Roguin, Ariel; Kobo, Ofer
Abstract: Objective: To assess the long‐term outcomes of patients with chronic inflammatory diseases who underwent percutaneous coronary intervention (PCI). Methods: A Retrospective cohort study of all adult patients who underwent PCI in a large tertiary care center from January 2002 to August 2020. Results: A total of 12, 951 patients underwent PCI during the study period and were included in the cohort. The population of chronic inflammatory diseases includes 247 (1.9%) patients; 70 with inflammatory bowel disease (IBD) and 173 with autoimmune rheumatic diseases (AIRD). The composite endpoint of mortality, acute coronary syndrome (ACS) or admission due to acute heart failure was similar at 30 days and more frequent in the inflammatory disease group (42.8% in AIRD group, 35.7% in the IBD group and 29.6% in the noninflammatory group, p < 0.0001). The adjusted cox regression model found a statistically significant increased risk of the composite primary endpoints of around 40% for patients both with AIRD and IBD. Readmission due to ACS was also increases at 30 days in the AIRD group compared to the noninflammatory group (0.6% vs. 0.1%, p < 0.001) and 1 year (37.6% for the AIRD group, 34.3% in the IBD group and 25.5% in the noninflammatory group ( p < 0.0001). Patients with inflammatory diseases were found to have a significantly increased risk congestive heart failure admissions at 1 year in a subgroup analysis of patients with myocardial infarction. Conclusion: Patients with AIRD and IBD are at higher risk for cardiovascular events in long‐term follow up once diagnosed with CAD and treated with PCI.